Protecting the Dispossessed: A Challenge for the International Community - Deng, Francis M. (Rowman & Littlefield Publishers, 2010)
An estimated 25 million people worldwide are internally displaceda significantly larger population than the 18 million refugees. Victims of civil wars, forced relocation, communal violence, natural and ecological disasters, and gross violations of human rights, they lack such human necessities as food, shelter, clothing, safety, basic health, and education. But because they remain inside their countries, they don't receive the same protection and assistance from the international community as those who cross borders and become refugees. Their plight, however, is drawing increasing international attention. In March 1992, Francis Deng was appointed Special Representative of the United Nations Secretary-General to study this harrowing situation. In this book, a substantially revised version of his report to the UN, Deng examines the causes and consequences of internal displacement, the legal standards for protection and assistance, enforcement mechanisms, the prevailing conditions in the affected countries, and the urgent need for an international response. In a compelling first-person narrative, Protecting the Dispossessed follows Deng's investigation and is based on interviews and information from governments, international organizations, individuals, and visits to several countries in Europe, Africa, and Latin America. Deng argues that sovereignty entails a responsibility to ensure the safety and welfare of the citizens and to protect fundamental human rights; the international community must uphold this standard and make violators accountable. While he acknowledges that steps are being taken in the right direction, he maintains that there is still much to be done. He presents a bold proposal, one that requires substantial changes in the international system, in the politics of major governments, and in the relations between states. He proposes a three-phase strategy aimed at monitoring conditions worldwide: to detect impending crises, ale